1998
DOI: 10.1159/000017904
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effect of Hamamelis Lotion in a UVB Erythema Test

Abstract: Background: Although Hamamelis virginiana has long been used in the traditional treatment of skin diseases, there are few controlled clinical studies defining the extent of its anti-inflammatory action. Objective:The anti-inflammatory efficacy of pH5 Eucerin aftersun lotion with 10% hamamelis distillate, the vehicle and a prior aftersun formulation were tested in 30 healthy volunteers using a modified UVB erythema test as model of inflammation. Methods: Four UVB doses ranging from 1 to 2 MED were evaluated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 6 publications
1
36
0
3
Order By: Relevance
“…In fact, 2 MEDs may be too strong an insult while 1 MED may be more useful to monitor the effects of an anti-inflammatory drug. However, in at least another experiment similar to ours, 2 MEDs proved to be effective in detecting the anti-inflammatory activity of topical drugs as weak as Hamamelis virginiana [15]. …”
Section: Discussionmentioning
confidence: 83%
“…In fact, 2 MEDs may be too strong an insult while 1 MED may be more useful to monitor the effects of an anti-inflammatory drug. However, in at least another experiment similar to ours, 2 MEDs proved to be effective in detecting the anti-inflammatory activity of topical drugs as weak as Hamamelis virginiana [15]. …”
Section: Discussionmentioning
confidence: 83%
“…One of the components of the patientʼs ink was H. virginiana, a kind of witch hazel that has been linked to anti-inflammatory properties, especially in cases of photodermatitis [37,38,39,40] and colonic cancer [41,42], due to a molecule called hamamelitannin, with anti-TNF properties (in vitro inhibition of TNF-mediated cell death and DNA fragmentation) [43] and scavenging activity against reactive oxygen species [42,44,45]. Even if it were attractive to assume that H. virginiana could have had an inhibitory effect over the purpuric rash, we would have to presume that functional levels of the active principle still remained in the skin 5 years after its injection, which is to be proven.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of vascular permeability and a vasoconstrictor effect have been observed in animal studies [16]. Reductions in cutaneous blood flow and skin temperature have also been demonstrated in humans [17,18], as has a reduction in UV erythema [19,20]. Studies by the authors using an experimental irritation model (sodium lauryl sulfate irritation test) showed that HM produced significant reductions in skin redness (chromametry a*-value) and cuta- Gloor/Reichling/Wasik/Holzgang neous blood flow (laser doppler).…”
Section: Discussionmentioning
confidence: 99%